The Relationship Between Non-Rebreathing Mask Oxygen Therapy Techniques and Oxygen Saturation in Patients with Respiratory Disorders in the ICU of Bhayangkara Hospital, Gorontalo - Jumiati Subaeda; Haslinda Damansyah; Rini Asnawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the technique of administering Non Rebrhiting Mask oxygen therapy to oxygen saturation in patients with respiratory disorders in the ICU room of Bhayangkara Gorontalo Hospital. This study uses a quantitative methodology with a quasi-experimental design, by applying a pre-test-post-test format of one group. This study showed that the average sex of respiratory patients at Bayangkara Hospital was male bel rjelnis kellamin (36.1%). And for the average age of respiratory disorders in Bayangkara Hospital, which is 40-50 years (44.4%). The average oxygen saturation value of cellbellum was carried out by Telrapi Telrapi Oxygeln Non Relbrhiting Mask 91.86%. Seldangkan selelpas Telrapi Oxygeln Non Relbrhiting Mask with a 96.00% oxygen saturation rate. There is a Telkhnik Pelmbelrian Telrapi Oxygeln Non Relbrhiting Mask on Oxygen Saturation in Respiratory Disorders at Bayangkara Hospital, which is a P-value value of 0.000.